2018
DOI: 10.1038/s41398-018-0224-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-9, miR-153 and miR-124 are down-regulated by acute exposure to cocaine in a dopaminergic cell model and may contribute to cocaine dependence

Abstract: Cocaine is one of the most used psychostimulant drugs worldwide. MicroRNAs are post-transcriptional regulators of gene expression that are highly expressed in brain, and several studies have shown that cocaine can alter their expression. In a previous study, we identified several protein-coding genes that are differentially expressed in a dopaminergic neuron-like model after an acute exposure to cocaine. Now, we used the prediction tool WebGestalt to identify miRNA molecules potentially involved in the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…We specifically focused on miR-124, miR-181 and miR-212, given that among many potentially relevant miRNAs, these have been the most explored by pre-clinical studies, with evidence indicating that: (1) these miRNAs are dynamically affected by cocaine acute exposure in both in vivo (e.g. rodent brain) and in vitro studies with neuronal and dopaminergic cell populations (Cabana-Domínguez, Arenas, Cormand et al, 2018;Chandrasekar & Dreyer, 2009;Xu, Wang, Lv et al, 2013); (2) they are molecular markers of the effects of chronic cocaine exposure in the brain reward system (Chandrasekar & Dreyer, 2011;Eipper-Mains, Kiraly, Palakodeti et al, 2011;Quinn, James, Hawkins et al, 2018); (3) they are suitable for the identification of vulnerable/resilient subjects to cocaine dependence in behavioral animal models of drug addiction (Chandrasekar & Dreyer, 2011;Im, Hollander, Bali et al, 2010;Quinn, Brown, Goldie et al, 2015;Viola, Wearick-Silva, De Azeredo et al, 2016); and (4) the manipulation of these miRNAs in the brain resulted in altered cocaine-induced neuroplasticity and behavioral phenotypes (Doura & Unterwald, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We specifically focused on miR-124, miR-181 and miR-212, given that among many potentially relevant miRNAs, these have been the most explored by pre-clinical studies, with evidence indicating that: (1) these miRNAs are dynamically affected by cocaine acute exposure in both in vivo (e.g. rodent brain) and in vitro studies with neuronal and dopaminergic cell populations (Cabana-Domínguez, Arenas, Cormand et al, 2018;Chandrasekar & Dreyer, 2009;Xu, Wang, Lv et al, 2013); (2) they are molecular markers of the effects of chronic cocaine exposure in the brain reward system (Chandrasekar & Dreyer, 2011;Eipper-Mains, Kiraly, Palakodeti et al, 2011;Quinn, James, Hawkins et al, 2018); (3) they are suitable for the identification of vulnerable/resilient subjects to cocaine dependence in behavioral animal models of drug addiction (Chandrasekar & Dreyer, 2011;Im, Hollander, Bali et al, 2010;Quinn, Brown, Goldie et al, 2015;Viola, Wearick-Silva, De Azeredo et al, 2016); and (4) the manipulation of these miRNAs in the brain resulted in altered cocaine-induced neuroplasticity and behavioral phenotypes (Doura & Unterwald, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This process appears to be cocaine and self-administration specific, as food self-administration has no effect on the internalization of neuronal exosomes in astrocytes and cocaine extinction reversed the reduced internalization of neuronal exosomes in astrocytes. In parallel, it has been reported that several neuronal miRs, including miR-124-3p, are down-regulated by cocaine exposure (Cabana-Dominguez et al, 2018). It is thus conceivable that the reduced miR-124 signaling, including reduced transfer from neurons to astrocytes through exosomes, underlies cocaineinduced down-regulation of GLT1 expression.…”
Section: Discussionmentioning
confidence: 95%
“…A study performed using the neuroblastoma SH‐SY5Y cell line found that 30‐min and 6‐hr cocaine treatments revealed a total of 90 differentially expressed miRNAs (Cabana‐Domínguez, Arenas, Cormand, & Fernàndez‐Castillo, 2018). The most significantly downregulated of these were miR‐9‐5p, miR‐101‐3p, miR‐124‐3p, miR‐124‐5p, miR‐137, miR‐153‐3p, and miR‐369‐3p.…”
Section: Psychostimulantsmentioning
confidence: 99%
“…Keller et al post‐validated miR‐1224 and miR‐6216 as significantly upregulated and miR‐130a‐3p and miR‐9a‐3p as significantly downregulated. While none of these miRNAs has been behaviorally confirmed to be relevant in nicotine addiction, miR‐9a‐3p has also been identified in cocaine and METH addiction, perhaps suggesting it for further nicotine addiction studies (Cabana‐Domínguez et al, 2018; Gu et al, 2020). Among the miRNAs reported by Keller et al (2018), it is important to note that, despite not being post‐validated, miR‐140‐3p, miR‐140‐5p, and miR‐125a‐5p were also seen to be significantly upregulated in their microarray data.…”
Section: Psychostimulantsmentioning
confidence: 99%